Forgery detection using Krawtchouk moments - Alenezi, Ahmad M.; Sapar, Siti Hasana; Rakhimov, I. S. (Pushpa Publishing House, 2019)
In this paper, we propose a method for processing image forgery detection using the Krawtchouk moments. The proposed method detects copy move forged regions of images by using Krawtchouk moments. Krawtchouk moments are used to extract features from the images to be used to identify the similar patches.